Mapping Environment, Society and Governance Awareness in Nepali Banks: Insights from Quantitative Research - Bashyal , Nirupama; Chalise, Mahananda (Quest Journal of Management and Social Sciences, 2024)
Purpose: This study explores the current state of ESG practices in Nepal. Given the limited research on ESG issues in the country and Nepal's commitment to achieving net zero emissions, this topic has gained significant relevance. Objectives: The study evaluates ESG awareness and determines which ESG factors are the least or most understood. Methods: A quantitative approach was employed, gathering primary data through a questionnaire. Descriptive analysis, correlation analysis, and ANOVA tests were conducted using SPSS to conclude. Stratified random sampling was used, and the sample size was 392. Finding: The findings revealed moderate ESG awareness, with a greater understanding of environmental and social indicators. Conclusion: This study lays the groundwork for future research on ESG practices in Nepal's banking and other sectors and serves as a stepping stone for developing policies and strategies to leverage ESG in supporting the attainment of sustainable development goals. Keywords: Sustainable development, sustainability, environmental, social, governance